mirzohidjon wrote:

But that is the problem,

I got the same answer as you, but official answer says the solution is B

63/20

well well well .....if we dont simplify the expression then we get 63/20

\(\sqrt{x^2 + 6x + 9}\) = \(\sqrt{(9/16 + 18/4 + 9)}\) = \(\sqrt{(9+72+144)/16}\) = 15/4

\(\sqrt{y^2 -2y +1}\) = \(\sqrt{4/25 - 4/5 + 1}\) = \(\sqrt{(4 - 20 + 25)/25}\) = 3/5

so we have

15/4 - 3/5 = (75 - 12)/ 20 = 63/20

Can someone please let me know what is wrong with the solution provided by simplifying the square roots??